Causality between Indian Futures and Cash Markets - Analysis with Granger Causality Block Exogenity Model - Jose, Babu; Lazar, Daniel (Asian Business Review, 2015)
In India, spot market return, number of contracts, turnover and volatility of the futures market are having short run relationship with futures market return. On the basis of the empirical analysis it is clearly found that spot market is the key factor that predicts the movement of futures market and the trader can depend upon volatility and trading volume to take any decision on futures market trading. In precise, spot market return, volatility of the futures market, turnover and number of contract are the determinants of the futures market in India. Spot market return is the major determinants of the futures market, indeed variables from futures market itself like open interest and turnover of futures market can be taken into consideration for determining the futures market return. The empirical study is made with spot return, futures return, volatility of futures return, number of contract, trading volume and open interest of S&P CNX Nifty and its underlying index Nifty -50 for the period 12th June 2000- 30th June 2011by applying the VAR Granger Causality/Block Exogeny Test. JEL Classification Code: G13